DISPUTE SETTLEMENT OF INDUSTRIAL RELATION OF PT. HAENGNAM SEJAHTERA INDONESIA IN THE MEDIATION STEP OF DINAS TENAGA KERJA OF KABUPATEN BOGOR - Omon Remen; Endeh Suhartini; ani yumarni (JURNAL HUKUM DE'RECHTSSTAAT, 2018)
Importance of law development Indonesia especially about law of labor will bring a positive issue for industriaI people. Industry as a one of economic center should have regulation to resolve conflict happens within production process. This research is to know the solution of industrial relation conflict which is done by labor union, based on Law No. 2 of 2004 about Industrial Relation Dispute Settlement, to advocate dispute The method for this research is by using normative empirical approach towards Laws and regulation, or literatures and field study to one of the private companies in Kabupaten Bogor. Conclusion of this research is that procedures to settle the dispute of industrial relation done by labor union in accordance with Law No 21 Tahun 2004 are: 1) Bipartite negotiation. 2) Authorized institution of manpower (mediation, conciliation, and (arbitration). 3). Industrial Relation Courts